Parasite-Derived Proteins for the Treatment of Allergies and Autoimmune Diseases - Wu, Zhenyu; Wang, Lifu; Tang, Yanlai; Sun, Xi (Frontiers in Microbiology, 2017)
The morbidity associated with atopic diseases and immune dysregulation disorders such as asthma, food allergies, multiple sclerosis, atopic dermatitis, type 1 diabetes mellitus, and inflammatory bowel disease has been increasing all around the world over the past few decades. Although the roles of non-biological environmental factors and genetic factors in the etiopathology have been particularly emphasized, they do not fully explain the increase; for example, genetic factors in a population change very gradually. Epidemiological investigation has revealed that the increase also parallels a decrease in infectious diseases, especially parasitic infections. Thus, the reduced prevalence of parasitic infections may be another important reason for immune dysregulation. Parasites have co-evolved with the human immune system for a long time. Some parasite-derived immune-evasion molecules have been verified to reduce the incidence and harmfulness of atopic diseases in humans by modulating the immune response. More importantly, some parasite-derived products have been shown to inhibit the progression of inflammatory diseases and consequently alleviate their symptoms. Thus, parasites, and especially their products, may have potential applications in the treatment of autoimmune diseases. In this review, the potential of parasite-derived products and their analogs for use in the treatment of atopic diseases and immune dysregulation is summarized.